Exploring Traditional Wild Edible Plants - book review - Permatasari, Ni Kadek Dewi (Ethnobotany Research and Applications, 2025)
A review of Vibhor Agarwal, Sachidanand Singh, and Rahul Datta. 2025. Exploring Traditional Wild Edible Plants. CRC Press, Taylor & Francis Group. Boca Raton, Florida, USA; and Abingdon, Oxfordshire, UK. pp. 357. GBP £160.00 (hardback), ISBN 978-1-032-49886-7 (hardback), ISBN 978-1-032-49889-8 (paperback), ISBN 978-1-003-39593-5 (ebook). The book Exploring Traditional Wild Edible Plants can serve as a comprehensive guide that explores the diversity and potential of wild plants in the contexts of food, ethnomedicine and pharmacology. Employing a multidisciplinary approach, it presents an in-depth discussion of ethnobotanical studies, phytochemicals, therapeutic benefits, nutritional value and toxicity aspects of wild edible plants. In addition, the book examines the sustainable utilization of wild edible plants and addresses key conservation challenges, such as overexploitation and habitat destruction.